FUNGSI DAN KEDUDUKAN HIKAYAT NABI BERCUKUR - Ani Diana, author (JURNAL PESONA, 2015)
The Tale of Propert Shave (TPS) is a work of prose figured legends. The tale comes from Persian Arabic that is re-constructed by taler glorifying the majestic of Prophet Mohammed as the last prophet of age. This research used several methods suitable with the stages of research, those are; (1) stage of collecting data; (2) stage of analyzing data; (3) stage of judgement and elimination data; (4) stage of comparison; (5) stage of editing; and (6) stage of translating.Keywords: Script, Editing, Classification